DAMPAK KINERJA TEKNOLOGI INFORMASI TERHADAP KUALITAS SISTEM INFORMASI - Estuningsih, Estuningsih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
This research is a study at a private company in Surabaya and Sidoarjo which has appliedinformation technology in carrying out their business operational. The primary purpose of thisresearch is to analyze the influence of information technology performance to the quality ofinformation system. This research gives managerial implication of steps which should be taken by acompany which applies information technology in order to improve information technologyperformance so it will generate a better quality of information system.The population in this research is companies which apply information technology in carryingout their business operational which are located in Surabaya and Sidoarjo. 4 (four) companies are usedas samples in this research. As much as 150 people who come from these 4 companies are taken assamples, with the criteria as the users of information technology i.e. the business employees which theinformation system is built for them. Only as much as 140 samples can be processed as the data, itmeans that only 93% of the total samples areappropriate to be used as data. The suitability of theserespondentsâ answering data are analyzed by using research models which are developed fromtheoretical mind frame by using SEM confirmatory analysis.It can be seen from the result of data analysis that hypothesis is accepted, it indicates that theperformance of information technology has positive influence to the information system quality whichis generated by the information technology. Plan and Organize, Acquire and Implement, Delivery andSupport, and Monitor and Evaluate variables are the performance of information technology indicatorwhich is capable to form a good model.Keywords : Information Technology Performance, Information System Quality, Plan andOrganize, Acquire and Implement, Delivery and Support, and Monitor andEvaluate.